2018
DOI: 10.1093/jxb/ery339
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a redox-dependent regulatory network of miRNAs and their targets in wheat

Abstract: A redox-dependent regulatory network of miRNAs and their targets were created using sequencing results, bioinformatics tools and correlation analysis of the examined biochemical and molecular parameters in wheat.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 58 publications
2
15
0
Order By: Relevance
“…The changes in the size of the glutathione pool (GSH+GSSG) and the GSSG/GSH ratio resulted in a daily oscillation in the half-cell reduction potential with an amplitude of about 20 mV (Supplementary Figure S3), which can greatly influence the function of redox-sensitive proteins. As observed earlier in wheat [64], a moderate increase could be detected in the GSH content during the light period, and high expression of HvAPSR in the meantime could contribute to this change by allowing a higher rate of Cys formation during the sulfate reduction and providing sufficient Cys for GSH synthesis. The low R/FR ratio increased both the expression of HvAPSR and Hvγ-ECS and the amount of Cys and GSH, indicating the spectral control of these genes and metabolites.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…The changes in the size of the glutathione pool (GSH+GSSG) and the GSSG/GSH ratio resulted in a daily oscillation in the half-cell reduction potential with an amplitude of about 20 mV (Supplementary Figure S3), which can greatly influence the function of redox-sensitive proteins. As observed earlier in wheat [64], a moderate increase could be detected in the GSH content during the light period, and high expression of HvAPSR in the meantime could contribute to this change by allowing a higher rate of Cys formation during the sulfate reduction and providing sufficient Cys for GSH synthesis. The low R/FR ratio increased both the expression of HvAPSR and Hvγ-ECS and the amount of Cys and GSH, indicating the spectral control of these genes and metabolites.…”
Section: Discussionsupporting
confidence: 70%
“…Thus, the GSSG accumulating during the light period can be regenerated by ascorbate peroxidase in the dark. High transcript levels of HvCAT2, HvCAT4 and HvPRX in cycling W light possibly cause a subsequent increase in the enzyme activity during the light period, as observed previously in wheat and Arabidopsis [30,64]. As described for HvGST and HvGR, maximum transcript levels of HvAPX1, HvAPX4, HvCAT2, HvCAT4 and HvPRX1 were also greater in low R/FR compared to W and supplemental B light during light/dark cycles, which further confirms the coordinated regulation of the various antioxidant genes by R and FR lights.…”
Section: Discussionsupporting
confidence: 59%
“…Cold stress [166] Wheat (Triticum aestivum) multiple miRNAs Reactive oxygen species (ROS) response [167] multiple miRNAs Water deficit and heat stress [168] TaemiR408…”
Section: Micrornas Stress Responses Referencementioning
confidence: 99%
“…miRNA are not coding RNA, which regulate gene expression at a post-transcriptional level in a suppressing mode [ 43 , 44 ]. The expression of miR395 is regulated under different abiotic stresses such as during sulfur starvation and drought [ 45 , 46 , 47 ]. Liang and co-workers demonstrated that miR395 modulates the accumulation of sulfate in rice by directly targeting the transcripts of ATPS and low affinity sulfate transporters [ 48 ].…”
Section: Resultsmentioning
confidence: 99%